O discurso e a prática do Ecoturismo na visão desenvolvimentista em Comunidades de Quilombolas em Goiás, Brasil - Karla Maria Silva de Faria; Maria Geralda de Almeida (Confins)
The objective was to reflect about the transformations condition of internal colonialism, reverberated in ecotourism practices in the Quilombola-Kalunga Historical Heritage Site, in Goiás. This site has been adapted to meet the growing demand for tourism and the assimilation and containment of environmental degradations that accompany the increase in tourist visitation, which predominantly aims at accessing areas of scenic beauty associated with waterfalls and viewpoints. The results indicate that this adaptation has moved away from the ideological ecotourism principles, as the profile of tourists has changed in recent years and the highlight is on natural attractions and some cultural aspects, which results in internal and external conflicts and still establishes development.